Nerve supply of the subscapularis during anterior shoulder surgery: definition of a potential risk area - Leschinger, Tim; Zeifang, Felix (Archives of orthopaedic and trauma surgery, 2017)
Purpose: The purpose of the study was to evaluate the position of the subscapular nerves relative to surgical landmarks during exposure and to analyze the pattern of innervation of the subscapularis to avoid injury during anterior shoulder surgery. Methods: 20 embalmed human cadaveric shoulder specimens were used in the study. The muscular insertions of the subscapular nerves were marked and their closest branches to the musculotendinous junction and the coracoid process were measured in horizontal and vertical distances. In addition, the innervation pattern of each specimen was documented. Results: 14/20 specimens showed an innervation of the subscapularis with an upper, middle and lower subscapular nerve branch. Even though the nerve branches were in average more than 2 cm medial to the musculotendinous junction, minimal distances of 1.1-1.3 cm were found. The mean vertical distance as measured from the medial base of the coracoid to the nerve innervation point into the muscle was 0.7 cm for the upper nerve branch, 2.2 cm for the middle nerve branch and 4.4 cm for the lower nerve branch. Conclusions: The subscapularis has a variable nerve supply, which increases the risk of muscle denervation during open shoulder surgery. Dissection or release should be avoided at the anterior aspect of the subscapularis muscle more than 1 cm medial to the musculotendinous junction. In approaches with a horizontal incision of the subscapularis, splitting should be performed at a vertical distance of 3.2–3.6 cm to the coracoid base to avoid iatrogenic subscapular nerve injuries.